Pengaruh Karakteristik Spiritual Intelligence, Emotional Intelligence dan Tipe Kepribadian Terhadap Sikap Dosen Pasca Transformasi STAIN Jurai Siwo Metro Menjadi IAIN Metro - Lestari, Dwi Vita (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2020)
The purpose of this study is to determine the characteristics of respondents (lecturers) which are correlated and relevant with the types of characteristics of Spiritual Intelligence, Emotional Intelligence and Personality Types they have on the perceptions of lecturers regarding the transformation process of STAIN Jurai Siwo Metro into IAIN Metro. This type of research is quantitative. The nature of the research emphasizes numerical data (numbers) processed by statistical methods. While the research approach is carried out by describing the ex post facto. For data processing techniques using the validity and reliability test instruments using the product moment formula. Data analysis used in this research is the univariate analysis test, multivariate analysis test, classical assumption test, hypothesis test, and direct and indirect effect test. From the data processing techniques and data analysis carried out, the results obtained: Only 2% of the variance Y (Lecturer Attitude) can be explained by changes in the variables X1 (spiritual intelligence) and X2 (emotional intelligence) and X3 (personality type). From the research results, it can be concluded that the variable of Lecturer Attitude in the transformation of STAIN Jurai Siwo Metro into IAIN Metro is influenced by other factors by 98%. Another transliteration that the Lecturer Attitude variable in the transformation of STAIN Jurai Siwo Metro into IAIN Metro is influenced by other factors of 85.7%.Key words : Spiritual Intelligence, Emotional Intelligence, Personality Type, Attitude, Transformation